Rapport: Little effect on children's, adolescents', and adults' statement quantity, accuracy, and suggestibility. Issue 4 (2nd October 2018) - Sauerland, Melanie; Brackmann, Nathalie; Otgaar, Henry
Abstract: Rapport building is widely recommended in eyewitness interview situations and is a critical component in some interview protocols. However, empirical evidence on the effectiveness of rapport building on memory performance is scant. The current experiment examined the effects of different levels of rapport (none, minimal, extensive) on children's, adolescents', and adults' memory ( N  = 229). Participants viewed a video of a mock theft and received one of three possible rapport manipulations. They then provided a free narrative of what they had seen, followed by 18 cued (suggestive and nonsuggestive) questions. In general, we found limited evidence of positive effects of rapport building on statement quantity and accuracy across age groups. Adolescents did profit more from extensive rapport building compared to no rapport. In line with the idea of a linear development of memory measures with age, adolescents generally fell in-between the other two age groups across different memory measures. The current study encourages systematic experimental research on the effect of rapport building on eyewitness memory.